Vertebral formula and numerical variations in the spine of the Antarctic and southern South American penguins (Aves: Sphenisciformes) - Sosa, M. Alejandra; Acosta Hospitaleche, Carolina (Science, 2024)
Abstract The vertebral column in tetrapods consists of several constant regions, namely the cervical, thoracic, lumbar, sacral, and caudal regions. Each of these regions is characterized by a specific number of vertebrae, contributing to the overall vertebral formula. Supernumerary and/or missing vertebrae have only been sporadically mentioned for penguins, and the specific vertebral formula is only determined for some non-passeres orders. Variations in the anatomy and vertebral number of South American and Antarctic penguin species are evaluated here. Sixty-six specimens of Aptenodytes forsteri , Pygoscelis adeliae , P. antarcticus , P. papua , Spheniscus magellanicus , and Eudyptes chrysocome were examined to establish the vertebral formula for six South American and Antarctic species, reporting the type and frequency of the variations found in the generalized configuration. We found no intraspecific variation in respect of the number of cervical as well as cervicothoracic vertebrae in all penguin species studied. Intra- and interspecific variation occur in the thoracic, synsacral, and caudal regions comprising 6–7, 13–14 and 5–8 vertebrae, respectively. Particularly, the variations were found in the transitional zones between one region and another and/or between synsacral segments.